Implementation of Tawhid-Based Integral Education to Improve and Strengthen Hidayatullah Basic Education - Tri Sanyoto; Nazar Fadli; Rozi Irfan Rosyadi; Muthoifin (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study was to determine the Concept and Implementation of Tauhid-based integral Education in Hidayatullah Elementary and Secondary Education in Surakarta. The approach used in this research is qualitative. The type of this research is descriptive research. This research was conducted at the Madya Hidayatullah Campus, Surakarta with the methods of observation, interviews, and documentation. .data analysis techniques used through source classification, data reduction, data presentation, drawing conclusions and verification. The concept of Tauhid-Based Integral Education in Hidayatullah Elementary and Secondary Education in Surakarta refers to the concept of making Tawhid the basic source as well as the core value of education. The concept of the framework of integrating inner tawheed consists of internalization, socialization, application, expansion and protection. For implementation strategy is the integration of knowledge, system integration and institutional integration. Efforts were made to achieve the target of achieving the concept to the fullest by standardization, centralization and systemic integration in the management of education. With the basic method of recitation of recitations, tazkiyah and ta'limul kitab wa al wisdom education in Basic Education Implementation of Integral Education Based on monotheism is more focused on the aspect of cultivating Adab, while in Secondary Education other than the cultivation of adab, the provision of understanding has begun to be prioritized science as the basic capital to carry out taklif sharia.